2018
DOI: 10.1073/pnas.1803839115
|View full text |Cite
|
Sign up to set email alerts
|

Alleviating catastrophic forgetting using context-dependent gating and synaptic stabilization

Abstract: Humans and most animals can learn new tasks without forgetting old ones. However, training artificial neural networks (ANNs) on new tasks typically causes them to forget previously learned tasks. This phenomenon is the result of "catastrophic forgetting", in which training an ANN disrupts connection weights that were important for solving previous tasks, degrading task performance. Several recent studies have proposed methods to stabilize connection weights of ANNs that are deemed most important for solving a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
179
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(183 citation statements)
references
References 34 publications
3
179
1
Order By: Relevance
“…It might be suboptimal to always desynchronize all modules that are not currently task-relevant. As suggested by previous work (50), keeping the irrelevant modules at random states (partial gating) might be sufficient to eliminate catastrophic forgetting.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…It might be suboptimal to always desynchronize all modules that are not currently task-relevant. As suggested by previous work (50), keeping the irrelevant modules at random states (partial gating) might be sufficient to eliminate catastrophic forgetting.…”
Section: Discussionmentioning
confidence: 81%
“…Because weight change depends on co-activation of relevant neurons (12,69), this approach protects the weights from changing. For example, Masse et al (50) propose that in each of several contexts, a (randomly selected) 80% of nodes is gated out, thus effectively orthogonalizing different contexts. They showed that synaptic gating allowed a multi-layer network to deal with several computationally demanding tasks without catastrophic forgetting.…”
Section: Discussionmentioning
confidence: 99%
“…Our work is comparable to a recent approach to avoiding catastrophic forgetting by Nakano and Hattori (2017), in which the intermediate layers of a deep neural network are gated by patterns that differ by context. A paper by Masse, Grant, and Freedman (2018) has the similar idea of using CHL as a plausible deep representation of information, and applying "pseudopatterns" alongside their regular training patterns for better separation. Our experiments explain in more depth how these patterns are formed and employed throughout different stages of the learning process.…”
Section: Discussionmentioning
confidence: 99%
“…However, memory capacity is limited in this case, as old memories are quickly overwritten with new ones 36 . Various remedies have been proposed to alleviate forgetting in artificial neural networks during continual learning, including context-dependence and architectural modularity 37,38 , but it is unclear how these methods might operate in a more biologically-realistic setting.…”
mentioning
confidence: 99%
“…In this work, we propose a new class of context-dependent associative memory models, which we call context-modular memory networks, inspired by previous theoretical studies 37,45 and experimental findings 10,12,13,21,39,46 . In our model, memories are assigned to different contexts, defined by a set of active neurons and connections.…”
mentioning
confidence: 99%